Contabilidad y Sostenibilidad Ambiental en la Empresa Agropecuaria “Una Aproximación a un Caso de Valoración de Activos Biológicos de la Hacienda Villa Isabela SAS” (2019)
The article is supported in the research "Towards an accounting structure for the agricultural sector, pertinent to the exploitation of nature", (USTAColombia, Grupo INDERCON), and incorporates research from the classroom in the face of socioenvironmental problems due to the exploitation of nature and, ignoranceof their contributions, alterations and their environmental effects. In fact, traditional accounting recognizes the financial condition, without providing data on environmental sustainability; considering an accounting structure that complements agricultural accounting and is used to reveal environmental conditions and changes and, as an example, it was taken into account, information from the Hacienda Villa Isabela; whose accounting system is supported in commercial and manufacturing accounting, without recognition of the contribution of nature to the agricultural business and less on environmental impacts.The study takes in to account international standards (IFRS), in addition to the rationality on the value provided by nature, calculated and explained in the article.